Enhancing students' creativity through graphic art: A holistic approach at Pesantren Modern Insan Madani in Bandung - Ma'arij, Jian Al (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
Art education in modern Islamic boarding schools (pesantren) faces several challenges, including difficulties in presenting practical materials that are engaging and relevant for students. This study aims to identify effective strategies for presenting practical graphic art materials, specifically using stencil techniques, that are appealing and easily understood by students in modern pesantren. The research employs a descriptive qualitative approach. A series of learning activities, including direct demonstrations, discussions, and hands-on practice by ninth-grade students at MTs Insan Madani under the guidance of an art teacher, were conducted over three sessions. The results indicate that using stencil techniques as an affordable and straightforward alternative for graphic art practice can help overcome the limitations of expensive art tools and materials. Additionally, integrating Islamic values into art education is a crucial aspect that aligns with the principles of Indonesia's Merdeka Curriculum within the pesantren education context. By implementing these strategies and adopting a holistic educational approach that integrates spiritual and intellectual aspects, it is expected that teachers can more effectively present practical art materials in modern pesantren, enhance students' creativity and academic performance, and positively contribute to the development of art education in the pesantren environment.